Efektivitas Massage Endorphin Untuk Mengurangi Kecemasan Pada Ibu Hamil Menjelang Persalinan - Saryani, Widiya; Alpiah, Dini Nur (UI Scholars Hub, 2025)
Pregnancy is a biological process involving complex physiological and psychological transitions that demand high adaptability from women, especially approaching childbirth. Anxiety during the third trimester is frequently reported and is associated with increased cortisol secretion, which may negatively impact labor effectiveness. This literature review aimed to synthesize scientific evidence regarding the effectiveness of endorphin massage in reducing anxiety among pregnant women in the third trimester. The review used a systematic approach based on the PICO framework, covering studies published between 2021 and 2025. Databases such as PubMed, Google Scholar, and SINTA were used to identify quasi-experimental studies comparing endorphin massage interventions with no massage control groups. Five studies met inclusion criteria and were analyzed. The results demonstrated consistent reductions in anxiety levels after intervention, with significant decreases in Hamilton Anxiety Rating Scale scores and improvements in emotional well-being. Variations in treatment frequency and duration influenced the magnitude of anxiety reduction. Physiological mechanisms involved in endorphin massage include stimulation of mechanoreceptors, activation of the parasympathetic nervous system, and suppression of cortisol production, creating a state of relaxation beneficial for maternal health. The findings support the adoption of endorphin massage as a safe, non-pharmacological complementary intervention to reduce antenatal anxiety. Further randomized controlled trials are recommended to strengthen the evidence base and develop standardized clinical guidelines for its implementation.